Seismic observations of splitting of the mid-transition zone discontinuity in Earth's mantle. - Deuss, A; Woodhouse, J (2001)
The transition zone of Earth's mantle is delineated by globally observed discontinuities in seismic properties at depths of about 410 and 660 kilometers. Here, we investigate the detailed structure between 410 and 660 kilometers depth, by making use of regional stacks of precursors to the SS phase. The previously observed discontinuity at about 520 kilometers depth is confirmed in many regions, but is found to be absent in others. There are a number of regions in which we find two discontinuities at about 500 and 560 kilometers depth, an effect which can be interpreted as a "splitting" of the 520 kilometer discontinuity. These observations provide seismic constraints on the sharpness and observability of mineralogical phase transitions in the mantle transition zone.